2014
DOI: 10.1002/2013ja019633
|View full text |Cite
|
Sign up to set email alerts
|

Period and damping factor of Pi2 pulsations during oscillatory flow braking in the magnetotail

Abstract: , we compare the oscillation period and the damping factor of the plasma sheet flows with those of the Pi2 magnetic pulsations on the ground at auroral and midlatitudes near the local time of the conjugate ionospheric THEMIS footprints. Whereas the damping of the plasma sheet flows and of the pulsations on the ground occurs on the same time scales, the frequency of the pulsations is on average twice the frequency of the plasma sheet flows. We conclude that larger-amplitude ground pulsations at auroral latitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 75 publications
(81 reference statements)
0
30
0
Order By: Relevance
“…Therefore, a flapping wave could transfer part of its energy for excitation of ULF waves that supplement other mechanisms of ULF wave generation by means of magnetotail dynamic processes (e.g. Runov et al, 2014;Panov et al, 2014). The connection between magnetotail dynamics and ionosphere processes involves the generation of parallel current systems in the near-Earth region.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a flapping wave could transfer part of its energy for excitation of ULF waves that supplement other mechanisms of ULF wave generation by means of magnetotail dynamic processes (e.g. Runov et al, 2014;Panov et al, 2014). The connection between magnetotail dynamics and ionosphere processes involves the generation of parallel current systems in the near-Earth region.…”
Section: Discussionmentioning
confidence: 99%
“…These facts make it difficult to use plasma sheet velocity measurements to test whether the oscillations are harmonic. However, the statistically established fact that the signal from the oscillatory braking of fast flows in the near-Earth plasma sheet is transmitted down to Earth and is observed as Pi2 pulsations there [Panov et al, 2014b] allowed us to use ground magnetometer measurements near THEMIS footprints instead, thereby suggesting anharmonicity of the flow oscillations observed by THEMIS probes P1-P3 at 11-14 R E downtail.…”
Section: Discussionmentioning
confidence: 99%
“…The oscillatory braking of fast flows in the near-Earth plasma sheet is transmitted down to Earth and observed as Pi2 pulsations [Panov et al, 2014b]. With the help of the AM03 model, we identified the location of THEMIS probes' footprints to be between Rankin Inlet and Gillam/Fort Churchill, Canada [Panov et al, 2014a].…”
Section: Themis Observations and Theoretical Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flow bursts have often been treated as moving earthward and stopping within the plasma sheet, as has been seen in the MHD simulations of Birn and Hesse [] and Birn et al []. There is also a proposal that flow bursts oscillate back and forth in radial distance as they stop within the near‐Earth plasma sheet [ Wolf et al , ], and this proposal has been supported by oscillatory flows observed in the plasma sheet by Panov et al [, ].…”
Section: Introductionmentioning
confidence: 96%